2012
DOI: 10.1089/dia.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Automated Overnight Closed-Loop Glucose Control Under MD-Logic Artificial Pancreas in Patients with Type 1 Diabetes: The DREAM Project

Abstract: Closed-loop insulin delivery under MDLAP is a feasible and safe solution to control overnight glycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 22 publications
1
52
0
1
Order By: Relevance
“…Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 90%
“…Over the past 5 years, a number of studies have been carried out to assess the safety and efficacy of the MD-Logic system for overnight glucose control in children, adolescents, and adults in various settings (2,(12)(13)(14). Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 99%
“…The main aim is developing an artificial pancreas that has a low cost to be suitable for patients with type 1diabetes and artificial pancreas should be reliable with small size. There are many control techniques have been utilised for the artificial pancreas, such as PID control [20][21][22][23][24][25], adaptive control [26,27], model-predictive control [28], fuzzy logic control [29,30] and linear -quadratic Gaussian [25,31].…”
Section: Modelling An Artificial Pancreasmentioning
confidence: 99%
“…Some systems use insulin as well as glucagon in dual hormone artificial pancreas (AP) systems, 55 although clinical applicability at present for bi-hormonal systems is limited due to lack of stable glucagon preparations. Numerous studies have emerged testing AP control algorithms initially under clinical research settings, 56 subsequently to controlled diabetes camp use 55,57 and now being brought to home use. 58,59 These studies have shown exciting and promising data on improved glucose variability, increasing time in target BG range, and without an increase in hypoglycemia frequency or SH rates.…”
Section: Automated Insulin Deliverymentioning
confidence: 99%